ChemInform Abstract: Synthesis of Polysubstituted Pyridines via Reactions of Chalcones and Malononitrile in Alcohols Using Amberlite IRA‐400 (OH‐). Issue 5 (4th February 2014) - Bahrami, Kiumars; Khodaei, Mohammad M.; Naali, Fardin; Yousefi, Behrooz H.
Abstract Polysubstituted pyridine derivatives are synthesized through economical one‐pot multicomponent reactions of different α, β‐unsaturated ketones, malononitrile, and ethanol or methanol in the presence of Amberlite IRA‐400 (OH‐) as catalyst.